Prevalence of Anemia Among Pregnant Women Attending Antenatal Care in Dhamar Governorate, Yemen: A Cross-Sectional Study (Epidemiology, Biostatistics, and Public Health, 2025)
IntroductionAnemia, a chronic condition affecting millions globally, poses greater risks to pregnant mothers, particularly in regions like Yemen. However, data on pregnancy-related anemia in Yemen is scarce. This study aimed to gauge anemia prevalence in Yemen's Dhamar governorate, identifying associated pregnancy-related risk factors.MethodsThrough a questionnaire-based cross-sectional study involving a total of 157 pregnant participants, data on sociodemographics (age, education, income) and health history (gestational age, parity, hemorrhage) were collected. Utilizing SPSS v25, frequencies, percentages, and binary logistic regression (OR, AOR) with 95% confidence intervals (p
Keywords: anemia, pregnant mothers, Hb, cross-sectional study.